Atypical ECG Presentation of Hypertrophic Cardiomyopathy stimulating Acute Myocardial Infarction - Tamrakar, Rikesh; KC, Sanjay Singh (Journal of Karnali Academy of Health Sciences, 2021)
Hypertrophic cardiomyopathy (HCM) is an idiopathic disease of myocardium characterized usually by marked asymmetric myocardial hypertrophy without underlying pressure or volume overload. This can cause spectrum of anatomic and hemodynamic consequences ranging from being asymptomatic to sudden cardiac death. HCM can have various ECG changes including significant STT changes. Rarely, the condition may sometimes present with ST elevation of acute ischemic injury type stimulating myocardial infarction. We here present a case where the patient presented with ST elevation and was initially evaluated as myocardial infarction. Further detail evaluation ruled out acute the myocardial infarction and confirmed the diagnosis of HCM. Patient subsequently improved with the treatment. Appropriate clinical evaluation along with investigation will avoid wrong management and unwanted intervention.